1996
DOI: 10.1021/jm950294c
|View full text |Cite
|
Sign up to set email alerts
|

A Study of the Active Site of Influenza Virus Sialidase:  An Approach to the Rational Design of Novel Anti-influenza Drugs

Abstract: The development of sialidase inhibitor-based potential anti-influenza drugs using rational drug design techniques has been of recent interest. The present study details as investigation of the active site of influenza virus sialidase by using the program GRID in an attempt to design more potent inhibitors in the hope they will eventually lead to anti-influenza drugs. A number of different probes (amino, carboxy, hydroxy, methyl, etc) have been used in an effort to determine the functional groups most likely to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
73
0
2

Year Published

1999
1999
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(77 citation statements)
references
References 17 publications
2
73
0
2
Order By: Relevance
“…Once the structure of the TS is known for reactions with a single barrier, the GRID potential, in combination with automated procedures, [44] can be used for a fast screening of large databases in search of better TSAs. This approach has been proven to be successful in drug design [45] by focusing on the molecular recognition between enzymes and their substrates. A further refinement step, on the first set of candidates selected in this way, may be introduced for the design of haptens that will elicit optimal CAs.…”
Section: Discussionmentioning
confidence: 99%
“…Once the structure of the TS is known for reactions with a single barrier, the GRID potential, in combination with automated procedures, [44] can be used for a fast screening of large databases in search of better TSAs. This approach has been proven to be successful in drug design [45] by focusing on the molecular recognition between enzymes and their substrates. A further refinement step, on the first set of candidates selected in this way, may be introduced for the design of haptens that will elicit optimal CAs.…”
Section: Discussionmentioning
confidence: 99%
“…Several potent and selective inhibitors, e.g., oseltamivir carboxylate (Ro64-0802, GS4071) and zanamivir (Relenza, GG167), of the influenza NA have been discovered through structure-based rational drug design (19,21,46). Oseltamivir carboxylate, the active metabolite of oseltamivir phosphate (Tamiflu, Ro64-0796, GS4104), is a potent and specific inhibitor of influenza A and B virus NA (26,27,48).…”
mentioning
confidence: 99%
“…[5][6][7] A new class of antivirals, with a different mechanism of antiviral action, has been designed and developed to provide another approach to the control of influenza. 8,9 The compounds specifically inhibit the action of the viral neuraminidase enzyme, essential for replication of both type A and B viruses. The sites affected are conserved; thus, the antiviral action is independent of antigenic change.…”
mentioning
confidence: 99%
“…The sites affected are conserved; thus, the antiviral action is independent of antigenic change. 8,9 Zanamivir (GG167), a sialic acid analog, has been demonstrated to be efficacious in clinical trials in shortening the duration and reducing the severity of type A and B influenza illness. 10 Ex-perimental studies have suggested promise in the prevention of influenza.…”
mentioning
confidence: 99%